The role of product market regulations in the process of structural change - Julián Messina (European Central Bank (ECB), 2003)
The sectoral allocation of labor differs considerably across developed economies, even in the presence of similar patterns of structural change. A general equilibrium model that captures the stylized facts of structural change is presented. In this framework, product market regulations raise barriers to entry that hinder the development of sectors with income elastic demand such as service industries. Thus, the paper suggests that differences in the regulations of product markets might help explaining cross-country differences in the sectoral allocation of employment. Cross-country evidence discussed in the paper shows that this proposition is supported by the data for a sample of OECD countries. Additionally, the model shows that higher service prices and rents in regulated economies reduce labor supply, providing a rationale for the negative association between product market regulations and the employment rate previously found in the literature.
Keywords: O11; O41; L5; 330